Administration of growth factors for bone regeneration. (May 2012) - Yun, Ye-Rang; Jang, Jun Hyeog; Jeon, Eunyi; Kang, Wonmo; Lee, Sujin; Won, Jong-Eun; Kim, Hae Won; Wall, Ivan
Growth factors (GFs) such as BMPs, FGFs, VEGFs and IGFs have significant impacts on osteoblast behavior, and thus have been widely utilized for bone tissue regeneration. Recently, securing biological stability for a sustainable and controllable release to the target tissue has been a challenge to practical applications. This challenge has been addressed to some degree with the development of appropriate carrier materials and delivery systems. This review highlights the importance and roles of those GFs, as well as their proper administration for targeting bone regeneration. Additionally, the in vitro and in vivo performance of those GFs with or without the use of carrier systems in the repair and regeneration of bone tissue is systematically addressed. Moreover, some recent advances in the utility of the GFs, such as using fusion technology, are also reviewed.